1997
DOI: 10.1038/sj.mp.4000334
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene polymorphisms: ethnic difference and possible association with bipolar affective disorder

Abstract: There is some evidence suggesting that a polymorphism of variable number of tandem repeats (VNTR) in the second intron of the serotonin transporter (5-HTT) gene and another variation which lies 1.2 kb upstream of the promoter of the gene (5-HTTLPR) are associated with affective disorders. However, conflicting results have also been reported. We examined an allelic association of these two polymorphisms in a Japanese sample of 191 patients with affective disorders (142 bipolar and 49 unipolar) and 212 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
188
6
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(218 citation statements)
references
References 2 publications
18
188
6
6
Order By: Relevance
“…Although it has greater statistical power than family studies, its results can be spurious for loci that differ in their allelic frequencies between ethnicities. The 5-HTTLPR polymorphism is known to vary strongly between ethnicities (Gelernter et al, 1999;Greenberg et al, 2000;Kunugi et al, 1997), and we addressed this issue by only analyzing ethnically matched probands and three control groups. Our three control groups were derived from three different geographical locations, and we thus cannot completely rule out some degree of remaining hidden population stratification (despite lack of differences in allelic and genotypic frequencies among these samples), given the recent report by Hu et al (2006) that showed marked differences in allelic frequencies at the 5-HTTLPR locus between Caucasian populations, even though these were partially comprised of individuals with psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has greater statistical power than family studies, its results can be spurious for loci that differ in their allelic frequencies between ethnicities. The 5-HTTLPR polymorphism is known to vary strongly between ethnicities (Gelernter et al, 1999;Greenberg et al, 2000;Kunugi et al, 1997), and we addressed this issue by only analyzing ethnically matched probands and three control groups. Our three control groups were derived from three different geographical locations, and we thus cannot completely rule out some degree of remaining hidden population stratification (despite lack of differences in allelic and genotypic frequencies among these samples), given the recent report by Hu et al (2006) that showed marked differences in allelic frequencies at the 5-HTTLPR locus between Caucasian populations, even though these were partially comprised of individuals with psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…48,59 The 31 papers finally selected reported 43 studies related to the review objective in total since each paper frequently reported several separate studies. In total, 17 population-based studies 9,14,33,34,38,46,50,51,56,60,61,66,[68][69][70] and six family-based studies 12,32,42,53,63,74 were about 5-HTTLPR. A total of 16 population-based studies 27,33,35,38,41,47,[49][50][51]54,56,58,60,61,70,75 and four family-based studies 12,52,57,63 were about the intron 2 VNTR.…”
Section: Resultsmentioning
confidence: 99%
“…According to the forest plot of the 5-HTTLPR, Mynett-Johnson et al (2000), 12 Hauser et al (2003) 34 and Rotondo et al (2002) 9 stood apart as an apparent cluster. The forest plot of the intron 2 VNTR showed Kunugi et al, 38 Heiden et al (2000) 35 and Collier et al (1996b) 58 as an apparent cluster. However, we could not identify any particular characteristics shared by these studies that might cause them to stand apart.…”
Section: Discussionmentioning
confidence: 97%
“…Ethnicity and length of assessment might have also played a role in determining the heterogeneity among studies. Different allele frequencies between Caucasians and Asians, the s allele being present in 42% of Caucasians, but in 79% of Asians, 45 are a strong cause of heterogeneity. In fact, when Caucasians were analyzed separately, the heterogeneity disappeared but it still remained when Asians were analyzed Figure 4 Outcome data for l/l versus l/s and s/s in remission rate, response rate and response rate within 4 weeks in Caucasian subjects.…”
Section: -Httlpr and Ssri Meta-analysismentioning
confidence: 99%